The Unmet Need for Psychotropic Medication within the Migrant Population of Northern Ireland - A Record Linkage Study - Patel, Kishan (International Journal of Population Data Science, 2019)
Background A large proportion of people with mental ill-health do not receive the care that they require - constituting unmet need. Migrant populations are particularly at risk of not receiving necessary care for a range of reasons including perceptual differences and multiple barriers to health service. Main Aim This record linkage study compares the likelihood of people with poor mental health receiving psychotropic medication between migrant and settled communities and amongst different migrant groups in Northern Ireland. Methods A cohort of 78,267 people aged 16-64 who reported chronic poor mental health in the 2011 Census records was generated and followed for the next 12 months by linkage to a centralised prescribing dataset to determine rates of treatment. All individual and household attributes were derived from Census forms. Absence of a psychotropic medication prescription from the beginning of 2011 represented unmet need. Logistic regression analyses quantified the relationship between psychotropic medication and migrant status, while accounting for relevant demographic and socio-economic factors. Results Overall, 86% of the settled population with chronic poor mental health received at least one psychotropic medication during the study period, compared to 67% of the equivalent population of 1,736 migrants. Although migrants were 61% less likely than the settled community to report poor mental health (OR 0.39 (95% CI 0.37 - 0.41)), those reporting poor mental health were less than one-third as likely as to be on psychotropic medication in fully adjusted models. There also existed considerable variation between individual migrant groups, with uptake of medication lowest amongst the Lithuanian migrant group (OR 0.09 (95% CI 0.05 – 0.14)), and highest amongst German migrant group (OR 1.30 (95% CI 0.87 – 1.94)). Conclusion Although this study suggests substantial unmet need for treatment of poor mental health amongst the migrant population of Northern Ireland this may not represent the whole story. Differences between individual migrant groups suggest that other factors may also be at play including differing approaches to treatment, or alternative routes to treatment. The implications of the study will be discussed in the paper.